PENGARUH PEMBERIAN BISA NAJA SPUTATRIX TERHADAP KADAR INTERLEUKIN-2 SERUM DARAH MENCIT YANG DIINDUKSI BENZO(A)PYRENE - Gina Anindyajati; Bambang Budiono (Jurnal Matematika Sains dan Teknologi, 2009)
Cancer has become a global health problem arisen from exposure to benzo(a)pyrene. Interleukin-2 is one of immune system components believed to play roles in eradicating cancer. Cobra venom has antitumor effect and also contain protease which could boost up immune system. This research was aimed at analyzing Naja sputatrix venoms effect to increase interleukin-2 level in blood sera of mice induced by benzo(a)pyrene. Four group of Balb-C mice were used. The first group (control) and second group (treatment with Naja sputatrix venom) consist of 5 mices. There are 6 mices used in group 3 and 4, both were injected intramuscularly by benzo(a)pyrene (0,3L/0,01mL oleum oil) at day 1, 8 and 15. Three months after, observation was carried out to see changes occured in their liver and lungs. Naja sputatrix venom 0,1 mL (diluted in saline 1:100) was given to group 2 and 4 for 30 days. Blood was collected from all groups and centrifuge to form sera. Level of interleukin-2 in sera was measured by ELISA method. The results show that Group 2 has the highest mean level of interleukin-2 (136,837 pg/mL), and group 3 has the lowest (8,996 pg/mL). Level of interleukin-2 in group 4 is slightly higher than group 3 (10,632 pg/mL). Kruskal-Wallis analysis result come with Sig. 0,155; therefore shows no significance(p>0,05). It is therefore concluded that Naja sputatrix venom do not increase interleukin-2 level in blood sera of mice induced by benzo(a)pyrene